2018
DOI: 10.1186/s10194-018-0847-1
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated headache: broadening the approach to headache in children and adolescents, with supporting evidence from a nationwide school-based cross-sectional survey in Turkey

Abstract: BackgroundHeadache is a leading disabler in adults worldwide. In children and adolescents, the same may be true but the evidence is much poorer. It is notable that published epidemiological studies of these age groups have largely ignored headaches not fulfilling any specific set of ICHD criteria, although such headaches appear to be common. A new approach to these is needed: here we introduce, and investigate, a diagnostic category termed “undifferentiated headache” (UdH), defined in young people as recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
78
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 28 publications
16
78
3
3
Order By: Relevance
“…In contrast, Rho et al reported tension type headache as the most frequent type among Korean schoolchildren followed by migraine headache [21]. Undifferentiated headache in our cohort was scarce, only 7 cases 0.6% which is in disagreement with previous results in Turkey [25]. This discrepancy may be explained by that in our study we reviewed every case with headache to con rm the accurate diagnosis.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast, Rho et al reported tension type headache as the most frequent type among Korean schoolchildren followed by migraine headache [21]. Undifferentiated headache in our cohort was scarce, only 7 cases 0.6% which is in disagreement with previous results in Turkey [25]. This discrepancy may be explained by that in our study we reviewed every case with headache to con rm the accurate diagnosis.…”
Section: Discussioncontrasting
confidence: 98%
“…headaches. This was similarly documented by other studies where migraine headache was followed in frequency by other headache types [18,24,25]. In contrast, Rho et al reported tension type headache as the most frequent type among Korean schoolchildren followed by migraine headache [21].…”
Section: Discussionsupporting
confidence: 74%
“…26,34,60 However, several studies have compared the QoL of children with migraine and TTH in childhood and found no significant differences on any QoL subscale between two headache groups. 25,30 To gain more insight into the effect of different types of headache on the QoL, far greater efforts are needed.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] Some studies also compared the QoL of children with migraine with that of children with TTH and found no significant difference between the two groups. 25,30 There is an uncertainty regarding the determinants of QoL in children with headache due to methodological differences. For instance, some studies have considered only the effects of the headache-specific factors, such as age at onset, duration, severity of headache, and sociodemographic factors, on the QoL.…”
Section: Introductionmentioning
confidence: 99%
“…DiesenDatenisteinvalidierterFragebogenzugrundegelegt,der erstmals in einer epidemiologischen Studie in der Türkei eingesetzt wurdeundweltweitVerwendungfindet [5][6][7][8][9][10].InDeutschland wurde für die Altersgruppe der 9-bis 14-Jährigen eine Migräneprävalenz von 13,1 % und eine Prävalenz des Spannungskopfschmerzes von 17,6 % erhoben, wobei Mädchen sowohl eine höhere Kopfschmerzprävalenz wie auch eine höhere Kopfschmerzfrequenz berichteten [11]. In einer weiteren Studie aus Deutschland war die Inzidenz der Migräne bis zum 9.…”
Section: Introductionunclassified